Combined effect of obesity and uric acid on nonalcoholic fatty liver disease and hypertriglyceridemia. Issue 12 (March 2017) - Zhang, Shujun; Du, Tingting; Li, Mengni; Lu, Huiming; Lin, Xuan; Yu, Xuefeng
Abstract : Abstract: Hyperuricemia is associated with metabolic syndrome (MetS), but the association is often confounded by the shared background of obesity. We sought to explore the modifying effects of obesity on the association between uric acid (UA), MetS components, and nonalcoholic fatty liver disease (NAFLD). We conducted a cross-sectional study in a Chinese population of 10, 069 participants aged ≥20 years. Multiplicative interaction between obesity (BMI ≥25 kg/m 2 ) and elevated UA was assessed using an interaction term in a logistic regression analysis. The presence of additive interaction was assessed based on the relative excess risk due to the interaction (RERI) and the attributable proportion due to the interaction (AP). There was no evidence of a multiplicative interaction between obesity and elevated UA on MetS components and NAFLD. However, there was a strong additive interaction between obesity and elevated UA with regard to NAFLD (RERI of 6.47 [95% CI 3.42–9.53] for men and 5.87 [1.55–10.19] for women) and hypertriglyceridemia (RERI of 1.38 [0.57–2.20] for men and 1.38 [0.08–2.67] for women). In addition, 42% and 36% of the increased odds of NAFLD for men and women, respectively, can be explained by an interaction between obesity and elevated UA (AP of 0.42 [95% CI (0.30–0.54)] for men and 0.36 [0.17–0.55] for women). Similarly, the interaction accounted for 27% and 26% of the increased risk of hypertriglyceridemia for men and women (AP of 0.27 [0.14–0.41] for men and 0.26 [0.06–0.47] for women). In this population, obesity and elevated UA synergistically interacted to increase the risk of NAFLD and hypertriglyceridemia.